About the solution of ecological and economic problems in the field of industrial use of nature - S. M. Sukhorukova (Тонкие химические технологии)
The article is dedicated to the search of reasons, which do not allow to provide ecological and economic efficiency of industrial use of nature. The possibility of transfer to biosphere economy and cosmic ecology is proposed for consideration